HUBUNGAN PERILAKU PUBERTAS TERHADAP PRESTASI BELAJAR SISWA KELAS VI SDS DI KABUPATEN TANGERANG - Rahmanika Cahyani; Een Unaenah; Hamdah Siti Hamsanah Fitriani (Latifah Pres, 2019)
This research is motivated by the change in behavior of students entering puberty. This study was conducted to determine (1) the behavior of puberty, (2) learning achievement, (3) the relationship of puberty behavior to learning achievement in class VI SDS Tunas Harapan Tangerang Regency. This study uses a type of quantitative research with survey methods, while the techniques used are observation, interviews, documentation and questionnaires. The total population is 92 students in class VI in one private elementary school in Tangerang Regency with sampling techniques using purposive sampling for research as many as 30 students consisting of 10 students in class VI A, 10 students in class VI B, and 10 students in class VI C on the school. The research instrument used was questionnaires that had previously been tested for validity. Hypothesis testing is done using the Product Moment correlation formula, which begins with a normality test of the data obtained. Based on the results of the study, there is a significant positive relationship between the behavior of puberty (X) on learning achievement (Y). This is evidenced by the implementation of the Product Moment correlation test which yielded 0.479 in the interval 0.40 - 0.59 which means that it has a sufficient / moderate correlation. And for the hypothesis obtained data for the value of t count = 2.886 while t table 0.05 = 2.048. This shows that the value of t count> t table means the research hypothesis (H1) is accepted. From the results of this study, it can be concluded that there is an influence between the behavior of puberty on the learning achievement of SDS students in Tangerang Regency.